POLA KOMUNIKASI DAN HUBUNGAN ANTAR PEMAIN GAME ONLINE DALAM KOMUNITAS TEAM EMR (EWAKO MAKASSAR) - Dhiya Zielfita Munzier; Irwanto Irwanto (JURNAL BADATI, 2023)
Communication patterns are formed from the process of communication between two or more individuals who send each message to be understood. Through the process of inter-player communication is done online game Rules of Survival that goes with high intensity and with the same goal, they form patterns of communication. The purpose of this study were (1) to determine the pattern of communication among online game players Rules of Survival in a community Team EMR (Ewako Makassar) in fostering relationships among members, (2) to determine the factors that influence communication community members in their interaction and (3) to determine the Verbal and nonverbal messages are delivered in the community.This study uses descriptive qualitative research. The technique of collecting data through observation, interviews and documentation. This type of observation in this study is the observation of participation (participant observation), researchers actively participate directly in tracking the process of communication between online gamers Rules of Survival in the Community Team EMR (Ewako Makassar) in Makassar. Sampling method in this study using purposive sampling. The population is all online game players Rules of Survival. The sample is 5-player online game Rules of Survival at EMR Team community. Data analysis technique is done through the process of analyzing the data through data reduction, data presentation, and conclusion. From the research results can be known patterns of communication between members of the community who formed Team EMR is the communication patterns of stars or all channels. This communication patterns can strengthen interpersonal relationships between community members Team EMR (Ewako Makassar) in Makassar.